Multimodal mechanical stimulation reduces acute and chronic low back pain: Pilot data from a HEAL phase 1 study - Baxter, Amy L.; Thrasher, Anderson; Etnoyer-Slaski, Jena L.; Cohen, Lindsey L. (Frontiers in Pain Research, 2023)
Background: Effective non-opioid pain management is of great clinical importance. The objective of this pilot study was to evaluate the effectiveness of multimodal mechanical stimulation therapy on low back pain. Methods: 11 female and 9 male patients aged 22-74 years (Mean 41.9 years, SD 11.04) receiving physical rehabilitation for acute (12) or chronic (8) low back pain chose heat (9) or ice (11) to accompany a 20-minute session of mechanical stimulation (M-Stim) therapy (Registered with Clinicaltrials.gov NCT04494841.) The M-Stim was delivered in 12 possible repeating “therapy cycle” patterns by three vibration motors (50Hz, 100Hz, 200Hz) with amplitudes between 0.1-0.3m/s2. Ten patients used a contained motor chassis attached to a thermoconductive single-curve metal plate. The next 10 patients’ device had motors attached directly to a multidimensionally curved plate. Results: Mean pain on a 10cm Visual Analog Scale (VAS) with the first motor/plate configuration went from 4.9+/-2.3cm to 2.5+/-2.1cm (57% decrease, p=0.0112), while the second reduced pain from 4.8+/-2.0cm to 3.2+/-1.9cm (45%, p=0.0353). Initial pain was greater with acute injury (5.8+/-2.0cm v. 3.98+/-1.8, p=0.025) and for patients older than 40 (5.44 v. 4.52), but pain reduction was proportional for chronic and younger patientsThere was no significant difference between plate configurations. Conclusions: A Phase I clinical pilot investigation on a multi-motor multi-modal device was promising for drug free pain relief. Results suggested pain relief independent of thermal modality, patient age, or pain chronicity. Future research should investigate pain reduction over time for acute and chronic pain.